(untitled) (ResearchJet Journal of Analysis and Inventions, 2020)
This article analyzes Shodmonqul Salom’s poem "Hirmonlarim". It focuses on metaphors and their meanings. At the same time, the role of the poet’s work in the spirituality of young people is interpreted.